Sledovi pleistocenske poledenitve na Trnovskem gozdu - Žebre, Manja (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2013)
Trnovski gozd is a high karst plateau situated in the Dinaric Mountains of western Slovenia which was modified by glacial action in the Pleistocene. With our research we concluded that slopes with northern exposure and the footslope of the highest ridge of Golaki had an glacier up to 180 m thick with an area of 4.8 km2. Several outlet glaciers were found to have been drifting over a steep escarpment from the plateau to the valleys of Belca, Trebuša and on the Hudo polje plateau. There was no evidence of glaciation on southern exposed slopes. The equilibrium line altitude was established via the accumulation-area ratio method on an elevation of 1240 m.
Keywords: geomorfologija; geomorphology; ledena doba; ledeniki; pleistocen; Slovenia; Slovenija; Trnovo Forest Plateau; Trnovski gozd